A CLOSE-UP VIEW OF INDIAN-TAJIK POLITICAL COOPERATION: THE INDIAN PERSPECTIVE - RUDENKO, Elena (CENTRAL ASIA AND THE CAUCASUS, 2009)
Indian researchers cannot seem to arrive at a consensus about the prime tasks of the new relations between the newly independent republics of Central Asia, on the one hand, and the South Asian countries (particularly India and Pakistan), on the other. Some experts assert that the economic aspect prevails over the political and that India is primarily interested in economic trade cooperation with the Central Asian states and evaluates political (including ethnic, confessional, etc.) factors only on the basis of its economic interests. Other specialists, on the contrary, believe that during the 1990s India was in fact preoccupied with preventing political instability in the Central Asian region and not with economic cooperation with the Central Asian republics. Politics prevailed over economics. Only after the political situation in Central Asia became more stable did India start considering economic cooperation with the region.1 Whereby it is worth noting that Tajik-Indian contacts have been traditionally characterized by a clear prevalence of precisely the economic component. The migration of various groups to the Indian subcontinent over the centuries through or directly from the territory of present-day Tajikistan,2 unification of the Tajik and Indian regions within the same states (the Achaemenid Empire, Alexander Makedonsky’s Empire, Bactria, the Kushan Empire, the Hephthalite state, the state of the Gaznevids and Timurids, etc.), and even the rule in the South Asian Delhi Sultanate of the ethnic Tajik Gurid dynasty could not compare in terms of significance with the role of the cultural-civilizational and economic trade cooperation between both sides. Several researchers believe that this cooperation began as early as the Upper Paleolithic Age when the first economic relations arose between the bearers of the archeological cultures of South Tajikistan and North-West India.3 During the Bronze Age, the northern trade route of the cities of the Harappa Indus civilization passed through Badakhshan; and a Harappa trade colony—the site of the ancient town of Shortugai A (2200-2000 BC)—was discovered on the south banks of the Panj.4 Active economic contacts between the present-day territories of India-Pakistan and Tajikistan were established during the flourishing of the Kushan Empire and particularly in the late Middle Ages and recent times. This was when Tajikistan’s city centers and Tajik-populated Bukhara and Samarkand were drawn into large-scale economic (not only trade but also financial and credit) contacts with India and also began playing an active intermediate role in Indian-Russian trade.5